2022
DOI: 10.1155/2022/1968313
|View full text |Cite|
|
Sign up to set email alerts
|

Case Management Improves Satisfaction, Anxiety, and Depression of Patients with Pregnancy Loss after In Vitro Fertilization and Embryo Transfer

Abstract: Objective. Pregnancy loss has negative impacts on both the physical and the mental health of expectant mothers, which calls for an in-depth investigation. In this study, we examined the effects of case management on patients with pregnancy loss after in vitro fertilization and embryo transfer (IVF-ET). Methods. 100 participants that had suffered pregnancy loss after IVF-ET-assisted pregnancy from January 2019 to March 2020 were divided into routine care and case management groups, each with 50 cases. For the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A large number of studies at home and abroad show that couples receiving IVF-ET generally have anxiety and depression, and women's anxiety and depression are more serious than their spouses during the treatment cycle. [6][7][8] In addition to the particularity of sperm source of couples receiving sperm donation and assisted pregnancy, the psychological burden of their women is more obvious and complex than other infertility, and many economic, social, marital and family problems cause their anxiety and depression. 9 Some domestic scholars have reported that the anxiety level at different treatment stages of IVF is related to the treatment outcome, especially the standard score of anxiety during embryo transfer is significantly negatively related to pregnancy, indicating that anxiety affects the treatment effect to a certain extent and reduces the clinical pregnancy rate.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies at home and abroad show that couples receiving IVF-ET generally have anxiety and depression, and women's anxiety and depression are more serious than their spouses during the treatment cycle. [6][7][8] In addition to the particularity of sperm source of couples receiving sperm donation and assisted pregnancy, the psychological burden of their women is more obvious and complex than other infertility, and many economic, social, marital and family problems cause their anxiety and depression. 9 Some domestic scholars have reported that the anxiety level at different treatment stages of IVF is related to the treatment outcome, especially the standard score of anxiety during embryo transfer is significantly negatively related to pregnancy, indicating that anxiety affects the treatment effect to a certain extent and reduces the clinical pregnancy rate.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%